Priority based Distributed Scheduling for Congestion and Collision Avoidance in WSN - J.Raman, C; Visumathi James, Dr (International Journal of Engineering and Technology, 2018)
In wireless sensor network (WSN), data scheduling, is impeded by congestion and packet collision. In order to overcome these issues, in this paper, a Priority based Distributed Scheduling for Congestion and Collision Avoidance in WSN has been proposed. In this technique, the system in which data packets generated by sensor nodes are categorized into high and low priority based on the importance of the data and time stamp. To prevent collision, a receiver backed or initiated MAC protocol is applied. Further, the congestion status of the network is checked cluster wise and node with the least congestion level is selected as the head of cluster group (CH). If the congestion status is high, then distributed storage maintenance (DSM) mechanism is applied. According to DSM, some gateway nodes which are nearer to the CH are chosen and the high priority packets are sent to those nodes for storing using the packet exchange policy. With the help of simulation it has been proved that this approach minimizes the congestion and the intra cluster collisions.